2015
DOI: 10.6090/jarq.49.111
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Evaluation of Irrigation Management Projects in Egypt

Abstract: The fewer the water resources, the greater the demand and the more important water becomes. This applies in Egypt, where rainfall is rare and most of the country is desert, except for a narrow strip of cultivated land and urban areas along the Nile river course. Like other large rivers, the Nile Delta region is characterized by large tracts of rich fertile agricultural land, overpopulation and unique and delicate environmental conditions caused by mixing drainage and freshwater. Managing these unique natural r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Some of them indicate that their views rest on a sole case of the study area and are not meant to draw any general conclusion (El‐Agha et al, 2011; Moghazy et al, 2014; Osman, Bakeer, et al, 2016). Others attempt to capture a larger picture and reflect on the overall situation of areas developed under irrigation improvement programmes (Depeweg & Bekheit, 1997; Elshorbagy, 2000; Abou Kheira, 2009; Water Management Research Institute, 2009; Kotb & Boissevain, 2012; Dutta, 2013; Mostafa & Fujimoto, 2015; Awwad et al, 2016; Molle et al, 2016). Although the results of the assessments have not yet brought a consistent conclusion on the changes in efficiency and performance, Fuglie et al (2020) found in their study that “raising productivity of natural resources, rather than resource expansion, was of far greater importance to long‐run growth in the nation's food supply” (Fuglie et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Some of them indicate that their views rest on a sole case of the study area and are not meant to draw any general conclusion (El‐Agha et al, 2011; Moghazy et al, 2014; Osman, Bakeer, et al, 2016). Others attempt to capture a larger picture and reflect on the overall situation of areas developed under irrigation improvement programmes (Depeweg & Bekheit, 1997; Elshorbagy, 2000; Abou Kheira, 2009; Water Management Research Institute, 2009; Kotb & Boissevain, 2012; Dutta, 2013; Mostafa & Fujimoto, 2015; Awwad et al, 2016; Molle et al, 2016). Although the results of the assessments have not yet brought a consistent conclusion on the changes in efficiency and performance, Fuglie et al (2020) found in their study that “raising productivity of natural resources, rather than resource expansion, was of far greater importance to long‐run growth in the nation's food supply” (Fuglie et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…With limited, and even threatened, water resources, and rapidly increased water demand, Egypt is expected to face severe water shortage problem. According to Mostafa and Fujimoto (2015), "The total water used from various sources in Egypt is about 76.5 billion m 3 . The Nile River supplies 73% of this demand directly, while the remainder mostly comes indirectly from the Nile (the reuse)."…”
Section: Introductionmentioning
confidence: 99%